Gender perspective of globalization and human development: Evidence from individual-level data - Jayanti Behera; Dukhabandhu Sahoo (Asian Development Bank Institute (ADBI), 2024)
The objective of this study is to explore the gender dynamics of globalization and human development at the individual level by covering geo-socioeconomic factors in Odisha, India. The study uses primary data collected through a structured survey schedule from 579 individuals in Odisha. By using the beta regression model, the study found that both sociocultural and environmental globalization have a positive impact on human development at the individual level. However, neither economic nor psychological globalization has a significant impact on human development at the individual level. Further, as regards the gender perspective, the effect of environmental globalization on human development is stronger for females than males. However, the effect of psychological globalization on human development is weaker for females than for males. Females have lower levels of human development than males, while adults and middle-aged individuals have higher levels of human development than elderly individuals. Moreover, individuals from Other Backward Class (OBC), Scheduled Class (SC), and Scheduled Tribe (ST) categories have lower levels of human development than individuals from unreserved categories. Individuals belonging to Muslim and Christian communities have higher levels of human development than those belonging to Hindu communities. Individuals from joint families experience higher levels of human development than those from nuclear families. Additionally, individuals residing in urban areas have higher levels of human development than those living in rural areas. However, individuals living in tribal regions have lower levels of human development than those living in nontribal ones. From the findings, it can be seen that individuals from weaker sections of society (women, OBC, SC, and ST) have lower levels of human development. Hence, both state and local governments, nongovernment organizations (NGOs), and other pressure groups should provide education and healthcare facilities, as well as employment opportunities in a more inclusive way to these sections to improve their human development and achieve a more equitable society (in terms of gender equality) in the era of globalization. Additionally, since individuals from rural and tribal regions experience lower levels of human development, it is suggested that the government needs to improve the infrastructure facilities in rural and tribal regions to reap the benefits of globalization and human development.
Keywords: F6; O15; J16; D14; C25; 330; globalization; human development; gender; beta regression; India